The Role of Preference-Based Value Transplantability as A Mediation of Adaptive Selling, Salesperson Brand Personality Congruence, Positive Selling Ambiance to Salesperson Performance (Study at PT. Bank BNI (Persero)Tbk) - Kartikasari, Evi Dian (International Journal of Psychosocial Rehabilitation, 2020)
This study addresses the need to study adaptive selling, salesperson brand personality congruence, positive selling ambiance mediated by preference-based value transplantability on salesperson performance. A model was tested using survey data collected from consumer credit salespeople at PT Bank Negara Indonesia (Persero) Tbk, located in Palembang and Jakarta Senayan areas. The regression equation model is used to test the hypothesis.This research is expected to be able to show the influence of preference-based value transplantability that has an impact on salesperson performance as mediating adaptive selling, salesperson brand personality congruence, a positive selling ambiance interaction.By examining the effect of preference- based value transplantability in a sales context, this research is expected to contribute originality to the marketing literature.